The effect of verbal agreement marking on the use of null and overt subjects: a quantitative study of first person singular in Brazilian Portuguese - Eduardo Correa Soares; Philip H. Miller; Barbara Hemforth (Fórum Linguístico)
In a corpus study and two acceptability experiments, we investigated whether there is a preference for null or overt subjects with ambiguous (syncretic) and exclusive (unambiguous) verbs in Brazilian Portuguese (BP). Previous literature has proposed that BP (i) is deactivating the “Avoid Pronoun Principle” and (ii) is a partially pro-drop language, whose morphosyntactic contexts for null subjects are restricted. The corpus study and the acceptability experiments show that there is an effect of person syncretism in the verbal paradigm on the relative frequency of null subjects and on the acceptability of sentences with null subjects in the first-person singular: there is a tendency to avoid ambiguity due to null subjects with ambiguous verb forms, but only in contexts with competing antecedents. These results are analyzed in the light of a general theory of anaphora resolution (ARIEL, 1990, etc.), as resulting from a calculation taking into account the accessibility of potential antecedents and the cost of the anaphoric form (ALMOR, 1996).